2014
DOI: 10.1002/mrm.25510
|View full text |Cite
|
Sign up to set email alerts
|

Multivendor implementation and comparison of volumetric whole‐brain echo‐planar MR spectroscopic imaging

Abstract: Purpose To assess volumetric proton MR spectroscopic imaging of the human brain on multi-vendor MRI instruments. Methods Echo-planar spectroscopic imaging (EPSI) was developed on instruments from three manufacturers, with matched specifications and acquisition protocols that accounted for differences in sampling performance, RF power, and data formats. Inter-site reproducibility was evaluated for signal-normalized maps of N-acetylaspartate (NAA), Creatine (Cre) and Choline using phantom and human subject mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 49 publications
1
78
0
Order By: Relevance
“…These results may provide reference data for studies on patients with brain disorders, with appropriate consideration for scanner and pulse sequence differences. A recent study, however, showed that the volumetric EPSI sequence and the data processing used here can be implemented across multivendor MR scanners and resulted in comparable numerical results (Sabati et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…These results may provide reference data for studies on patients with brain disorders, with appropriate consideration for scanner and pulse sequence differences. A recent study, however, showed that the volumetric EPSI sequence and the data processing used here can be implemented across multivendor MR scanners and resulted in comparable numerical results (Sabati et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…These focuses have included: unedited, short-TE MRS (Deelchand et al, 2015); low-field MRS (Träber et al, 2006); ultra-high field MRS (van de Bank, 2015); absolute quantification (Bovée et al, 1998; De Beer et al, 1998; Keevil et al, 1998; Soher et al, 1996); MRSI (Sabati et al, 2015; Wijnen et al, 2010); body MRS (Bolan et al, 2016; Scheenen et al, 2011); brain tumor classification (García-Gómez et al, 2009; Julià-Sapé et al, 2006; Tate et al, 2003; Vicente et al, 2013); and HIV-associated dementia (Chang et al, 2004; Lee et al, 2003; Sacktor et al, 2005). Even for short-TE methods, the degree of agreement between sites and scanners is highly dependent on the degree of acquisition homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Although metabolite maps were not expressed in absolute concentrations, due to the requirement that this would greatly increase acquisition times, our approach provides normalized maps of individual metabolites using the interleaved water signal acquired during the 3D-EPSI sequence (8) as a reference that can be implemented across multiple sites (6). As a proof of concept, this study has validated statistical mapping analysis as applied to whole brain 3D-EPSI as an in vivo and non-invasive means to characterize the topography of metabolic disorders in neurological diseases and its relationship with clinical deficit.…”
Section: Discussionmentioning
confidence: 99%
“…While these methods provide improved spatial coverage there remain limitations for sampling of the entire brain (6). Nevertheless, partial brain sampling has been reported to be sufficient to conduct statistical mapping analyses comparing metabolic maps between different group of healthy subjects (7).…”
Section: Introductionmentioning
confidence: 99%